2015
DOI: 10.1155/2015/283958
|View full text |Cite
|
Sign up to set email alerts
|

A Disproportionate Burden of Care: Gender Differences in Mental Health, Health-Related Quality of Life, and Social Support in Mexican Multiple Sclerosis Caregivers

Abstract: Background. Multiple sclerosis (MS) rates in Latin America are increasing, and caregivers there experience reduced mental and physical health. Based on rigid gender roles in Latin America, women more often assume caregiving duties, yet the differential impact on women of these duties is unknown. Methods. This study examined gender differences in mental health (Patient Health Questionnaire-9, Satisfaction with Life Scale, Rosenberg Self-Esteem Scale, State-Trait Anxiety Inventory, and Zarit Burden Inventory), h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 52 publications
3
21
0
4
Order By: Relevance
“…In this study, we found that male caregiver gender predicted higher caregiver burden. A possible explanation could be that male caregivers often report having fewer resources and lower perceived social support than female caregivers (Perrin et al., ). Furthermore, researchers observed that higher caregiver burden in males is usually associated with harder physical care (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that male caregiver gender predicted higher caregiver burden. A possible explanation could be that male caregivers often report having fewer resources and lower perceived social support than female caregivers (Perrin et al., ). Furthermore, researchers observed that higher caregiver burden in males is usually associated with harder physical care (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies examined caregiver and/or care recipient characteristics involved with caregiver strain when providing informal care for a person with MS. From the caregiver's perspective, an increased ability to cope with caregiving and satisfaction with social support were associated with less caregiver strain (Knight et al, 1997), while a higher number of caregiving hours, more restrictions to the caregiver's ability to perform daily activities, higher carer anxiety, low household income and living with the care recipient were associated with higher caregiver strain (Buchanan et al, 2011;Giordano et al, 2016). Studies were inconsistent on whether male or female caregivers experience more strain (Buchanan et al, 2011;Giordano et al, 2016;Knight et al, 1997;Perrin et al, 2015). In terms of characteristics of the person with MS, the most distressing MS symptoms for spousal caregivers were motor problems and gait disturbance, sudden mood changes, the partner upsetting other people, incontinence and pain (Knight et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Interpersonal Support Evaluation List-12 was used to measure 3 aspects of social support including appraisal, belonging and tangible [27]. Interpersonal Support Evaluation List-12 originated from the Interpersonal Support Evaluation List developed by Sheldon Cohen in 1985 [49] and has been used repeatedly adopted in previous studies [50][51][52][53]. For each of the 3 included aspects, there were 4 related questions in the questionnaire.…”
Section: Part 1 -Dependent Variable -Presenteeismmentioning
confidence: 99%